Analisis Manajemen Pra Penempatan Tenaga Kerja Migran di PT Assalam Karya Manunggal - Nisak, Mahfirotul Choirotun; Damayanti, Yenie Eva (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the pre-placement management of migrant workers conducted by PT Assalam Karya Manunggal. The company operates in the field of migrant labor deployment, particularly to Asia and the Middle East. The pre-placement process is a critical stage in ensuring readiness, legality, and protection for prospective workers. This research uses a descriptive qualitative method, collecting data through observation, interviews, and document studies during the internship from January 13 to February 13, 2025. The results indicate that PT Assalam Karya Manunggal implements a pre-placement management system that includes administrative selection, training, legal documentation, and mental preparation. However, some obstacles were identified, such as delays in documentation and low legal literacy among prospective workers. The study recommends strengthening digital systems and increasing legal literacy to improve the efficiency and protection of migrant workers